TAHAPAN INDONESIA DALAM MENDAPATKAN STATUS OBSERVER DI FINASCIAL ACTION TASK FORCE (FATF) - Nopreza Pahlevi; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to describe the phenomena of money laundering and terrorism financing crimes in the world. The rise of cases of money laundering and terrorism financing prompted the G7 countries to form an international regime Financial Action Task Force (FATF). The aim of the FATF is to set standards and promote the effective implementation of legal, regulatory and operational measures to combat money laundering, terrorist financing and other related threats to the integrity of the international financial system.This research theoretically has built by using the perspective of neoliberalism with a focus on institutionalism aspects, and is supported by the theory of international organizations and strategy concept. Formulation of all arguments, data, facts, and theoritical framework in this research using qualitative explanation methods. This research also using nation-state as the level of analyze.This study aims to describe the steps taken by Indonesia in its efforts to gain observer status in the FATF. These steps were taken on the rationality that Indonesia was once included in the black list issued by the FATF for countries deemed uncooperative in the crime of money laundering and terrorism financing. The author will examine how Indonesia consistently implements the FATF Mutual Evaluation Review.Keywords : FATF, Anti Money Laundering, Terrorism Funding, FIU, NCCTs